Pelatihan Pembuatan Pestisida Nabati yang Ramah Lingkungan sebagai Upaya Pengendalian Hama Kakao pada Kelompok Tani Sahabat Tani di Desa Persiapan Wae Munde Kabupaten Manggarai NTT - Adi, Defiyanto Djami; Chourunnisa, Jessyca Putri; Wahyu, Yuliana; Dalle, Nautus Stivano; Sikone, Hilarius Yosef; Utama, Wigbertus Gaut; Bollyn, Yohana Maria Febrizky; Achmadi, Puspita Cahya; Ngoni, Maria Salestina (Jurnal Pengabdian UNDIKMA, 2026)
This community service program aims to improve farmers’ knowledge and skills in producing and applying botanical pesticides derived from lemongrass (Cymbopogon citratus) and betel leaves (Piper betle) as an environmentally friendly alternative for cocoa pest management. The program was implemented through educational outreach and hands-on training, with participant learning outcomes evaluated using pre-test and post-test assessments analyzed descriptively. The results demonstrated a high level of participant engagement throughout both the theoretical and practical sessions. Knowledge evaluation revealed a substantial improvement, with the average score increasing from 25% in the pre-test to 92% in the post-test, representing a 67-percentage-point gain. These findings indicate that the combination of lectures, group discussions, and practical demonstrations was effective in enhancing farmers’ understanding of the production and application of botanical pesticides. In addition to strengthening farmers’ capacities, the program introduced a safer, more affordable, and sustainable pest management alternative through the utilization of locally available natural resources.